Resistance of Andean beans and advanced breeding lines to root rots in Uganda - Amongi, W.; Kato, F.; Male, A.; Musoke, S.; Sebuliba, S.; Nakyanzi, B.; Naluwooza, C.; Acam, C.; Mukankusi, C. (African Crop Science Journal, 2020)
Root rots cause severe yield losses of up to >70% in common bean (Phaseolus vulgaris L.) in most parts of the world, with devastating effects on the major commercial bean cultivars in East and Central Africa. Increased intensity of droughts and rains, and higher temperatures influence the occurrence and distribution of root rots, resulting in increased epidemics. The causal pathogens tend to occur in a complex, and since most cultivars do not have broad resistance, adverse effects continue to occur. The objective of this study was to evaluate the levels of dual resistance of new breeding lines (BL) developed for root rot resistance, as well as Andean (ADP) genotypes, for resistance to Fusarium (FRR) and Pythium root rots (PRR). Altogether, 316 new BL developed for root rot resistance and 295 ADP bean genotypes were evaluated at Kawanda in Uganda. There were significant differences (P<0.05) among genotypes for both root rots and yield. Thirty and 1.9 percent of the BL and ADP genotypes expressed resistance to both root rots. In addition, more than 80% of ADP genotypes showed susceptibility to both root rots. Yield was generally poor with means of 458 kg ha-1 for ADP, and ranging from 949 to 1075 kg ha-1 for the BL groups. Nonetheless, the 0.3 and 2.4% of the ADP and BL that yielded >2000 kg ha-1 expressed high yield potential, considering that majority of the genotypes yielded below 1000 kg ha-1.
Keywords: Dual resistance, Fusarium, Phaseolus vulgaris, Pythium